Epidemiology and Trends of Pertussis among Infants: United States, 2000–2015 - Bozio, Catherine (Open Forum Infect Dis, 2017)
BACKGROUND: Pertussis, a cyclic respiratory disease, causes the greatest morbidity and mortality among infants, particularly those too young to be vaccinated. Following a resurgence of pertussis in the 1990s, a recommendation was made in 2012 to vaccinate during every pregnancy in order to prevent infant disease. We describe pertussis trends from 2000–2015 among U.S. infants aged <1 year. METHODS: We analyzed infant pertussis cases reported through the National Notifiable Diseases Surveillance System from 2000 to 2015. Incidence rates (cases per 100,000 population) among various age groups (<2, 2– <4, 4– <6, and 6–<12 months) were calculated using National Center for Health Statistics population estimates as denominators. Negative binomial regression was used to estimate the annual average percent change with a linear trend; P < 0.05 was significant. RESULTS: From 2000 to 2015, 48,909 infant pertussis cases and 255 deaths were reported; infants aged <2 months accounted for 38.7% of cases. The age distribution of infant cases was stable from 2000 to 2009 but changed from 2010 to 2015 (Fig. 1), as the proportion of cases aged 4–<12 months increased annually on average by 4.7% (P < 0.001). Annual incidence was highest among <2 month olds; however, rates increased among older infants (Fig. 2): 7% average annual increase among infants aged 4–<6 months and 11% among infants aged 6–<12 months (P < 0.001 for each). The proportion of infants hospitalized decreased over time in each age group (P < 0.001 for all) with the largest annual average declines among 4–<6 (−5.1%) and 6–<12 month (−5.9%) olds. For all age groups, hospitalization rates were relatively stable, but non-hospitalization rates increased (P < 0.05 for all). The case–fatality ratio (CFR) was highest among <2 month olds (1.6%); CFRs decreased over time among <2 and 2–< 4 month olds (P < 0.05 for each). CONCLUSION: Pertussis incidence remains highest among infants aged <4 months, although the age distribution appears to be changing. Decreasing proportions of infants hospitalized may suggest a true decline in disease severity or an increase in reporting of less severe disease. Ongoing monitoring of infant pertussis is needed to better understand the impact of vaccinating pregnant women to prevent pertussis in young infants. DISCLOSURES: All authors: No reported disclosures.